The Role of Customer Experience in Shaping Purchase Decisions: The Mediating Effect of Customer Engagement on Digital E-Commerce Platforms - Firdaus Firdaus; M. Rully Sjahirul Alim; Kukuh Mulyanto; Abdullah Abdullah; Asepta Hendriyanto; Nuruddin Mahmud; Fiderius Ismanto; Heru Yulianto; Alis Arifah Rahman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the effect of customer experience on purchase decisions, with customer engagement as a mediating variable in digital e-commerce platforms. Increasing competition in the e-commerce sector has shifted managerial focus toward experiential and relational factors influencing consumer decision-making. A quantitative approach was employed using survey data collected from e-commerce users through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that customer experience has a significant positive effect on both customer engagement and purchase decisions. Customer engagement also significantly mediates the relationship, indicating that improved experiences enhance purchasing outcomes indirectly through stronger engagement. However, the moderating effect between the variables is not statistically significant. The model demonstrates satisfactory explanatory power, indicating its robustness in explaining consumer behavior in digital platforms. These findings emphasize the importance of designing effective experience-based strategies to strengthen engagement and drive purchasing outcomes. This study provides practical insights for e-commerce managers and contributes to the literature on digital marketing and consumer behavior.